Neurotoxicity of Unconjugated Bilirubin in Neonatal Hypoxic-Ischemic Brain Injury in vitro - Dani, Carlo; Pratesi, Simone; Mannaioni, Guido; Gerace, Elisabetta (Frontiers in Pediatrics, 2021)
Background: The pathophysiology of bilirubin neurotoxicity in course of hypoxic–ischemic encephalopathy (HIE) in term and preterm infants is still poorly understood. We hypothesized that oxidative stress may be a common mechanism that link hyperbilirubinemia and HIE. Objectives: The objective of the present study was to evaluate whether unconjugated bilirubin (UCB) may enhance the HI brain injury by increasing oxidative stress and to test pioglitazone and allopurinol as new antioxidant therapeutic drugs in vitro. Methods: The effects of UCB were tested on organotypic hippocampal slices subjected to 30 min oxygen-glucose deprivation (OGD), used as in vitro model of HIE. The experiments were performed on mature (14 days in culture) and immature (7 days in culture) slices, to mimic the brains of term and preterm infants, respectively. Mature and immature slices were exposed to UCB, human serum albumin (HSA), pioglitazone, and/or allopurinol for 24 h, immediately after 30 min OGD. Neuronal injury was assessed using propidium iodide (PI) fluorescence. ROS formation was quantified by using the 2′,7′-dichlorodihydrofluorescein diacetate (DCF-DA) method. Results: In mature slices, we found that the neurotoxicity, as well as oxidative stress, induced by OGD were enhanced by UCB. HSA significantly prevented UCB-increased neurotoxicity, but had a slight reduction on ROS production. Allopurinol, but not pioglitazone, significantly reduced UCB-increased neurotoxicity induced by OGD. In immature slices exposed to OGD, no increase of neuronal death was observed, whereas oxidative stress was detected after UCB exposure. HSA, pioglitazone and allopurinol have no protective effects on both OGD-induced neuronal death and on UCB-induced oxidative stress. For this reason, UCB, pioglitazone and allopurinol was also tested on ischemic preconditioning protocol. We found that UCB abolished the neuroprotection induced by preconditioning and increased oxidative stress. These effects were restored by allopurinol but not pioglitazone. Conclusions: UCB characterized a different path of neuronal damage and oxidative stress in mature and immature hippocampal slice model of HIE. Management of hyperbilirubinemia in a complex pathological condition, such as HIE and hyperbilirubinemia, should be very careful. Allopurinol could deserve attention as a novel pharmacological intervention for hyperbilirubinemia and HIE.